HBR's 10 must reads on change management - Larkin, Susan; Clark, Bernard Setaro 1972- (Ascent Audio, 2022)
Most company's change initiatives fail. Yours don't have to. If you read (or listen to) nothing else on change management, listen to these ten articles (featuring "Leading Change," by John P. Kotter). We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you spearhead change in your organization. HBR's 10 Must Reads on Change Management will inspire you to: lead change through eight critical stages; establish a sense of urgency; overcome addiction to the status quo; mobilize commitment; silence naysayers; minimize the pain of change; concentrate resources; and motivate change when business is good. This collection of bestselling articles includes: featured article "Leading Change: Why Transformation Efforts Fail" by John P. Kotter, "Change Through Persuasion," "Leading Change When Business Is Good: An Interview with Samuel J. Palmisano," "Radical Change, the Quiet Way," "Tipping Point Leadership," "A Survival Guide for Leaders," "The Real Reason People Won't Change," "Cracking the Code of Change," "The Hard Side of Change Management," and "Why Change Programs Don't Produce Change."
Online resource; title from title details screen (O'Reilly, viewed November 22, 2022)
Keywords: Organizational change; Changement organisationnel; Audiobooks; Livres audio